PEMBERDAYAAN MASYARAKAT TENTANG PEMBERIAN MAKANAN PENDAMPING AIR SUSU IBU (MP-ASI) LOKAL - Kustiyati, Sri; Firrahmawati, Lely (P3M STIKES Aisyiyah Surakarta, 2017)
Age 0-24 months is a period of rapid growth and development, so often termed as a golden period as well as a critical period. Gold period can be realized if at this time the baby and children get the appropriate nutritional intake for optimal growth and development. To achieve optimal growth, within the Global Strategy for Infant and Young Child Feeding, WHO / UNICEF recommends providing complementary feeding (AI) foods from infants 6 months to 24 months. The recommendation emphasizes that socio-cultural MP-ASI should be made from cheap and easy-to-obtain food in the local area (indigenous food). Given the importance of socio-cultural aspects and aspects of community empowerment in the provision of MP-ASI, training will be held that is the training of local MP-ASI production or also called